“We’re all in the same storm, but not all of us are in the same boat”: qualitative exploration of UK response-focused civil servants experiences of working from home during COVID-19 - Charlotte E. Hall; Samantha K. Brooks; Neil Greenberg; Dale Weston (BMC Public Health)
Abstract Introduction The experiences of UK Government response-focused employees, who were considered frontline workers during the coronavirus response, are missing from current literature. Meeting the demands of being on the frontline, whilst also adjusting from a normal and practiced way of working to having to work from within one’s home, may bring a plethora of new barriers and facilitators associated with providing an effective pandemic response. Method This interview study collected and analysed data from 30 UK Civil servants who worked on the COVID-19 pandemic response from their own homes. Interviews aimed to: (1) explore UK Government employee’s experiences of working from home whilst contributing to the pandemic response; and, (2) establish what support and guidance employees were offered, and what they would recommend for future public health emergencies requiring homeworking. Results Seven themes were extracted from the data: overall experience of working from home; preparedness for working from home; experience of contributing to the response effort; work life balance; relationships with colleagues; space and equipment; and, inclusivity. Findings suggested that during the pandemic, participants reported feeling a strong sense of purpose and achievement for contributing to the response. But, the work was demanding, particularly for those who had to rapidly, and unexpectedly, transition from office or lab work to home working. More generally, the nature of their homeworking experience depended on a range of practical (e.g., space in the home), organisational (e.g., relationships with managers) and personal factors (e.g., caring responsibilities). Many participants were underprepared to work from home, but participants provided a plethora of information relating to what support offers they would find useful during future work on the frontline from their own homes. Conclusion The results of this study demonstrate that frontline UK Civil servants may need more tailored and flexible multilevel support (i.e., from peers, managers, organisations) during future public health emergencies when they are required to work from home. A series of data-informed recommendations are created and discussed.